2023
DOI: 10.1007/s10661-023-10957-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference of physicochemical quality elements of tropical lagoon Nokoué (Benin)

Abstract: Transparency (>0.9 m) . According to the System for the Evaluation of Coastal Water Quality, these thresholds correspond to "good to medium" suitability classes, except for total phosphorus. One of the original features of this study is the use of the bounds of the credibility interval of the fixed-effect coefficients as local weathering standards for the characterization of the physico-chemical status of this anthropized African ecosystem.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…We can also explain the negative in uence of dredging activities (Observation characteristic of this type of pressure proxy 'Depth') which likely lead to the suspension of sediment in the water column, by its abrasive effects on the eggs, by its reduction of the pumping rate of the bivalves and by their direct mortality (Wilber & Clarke 2001). In the context of Nokoué, resuspension is also driven by waves (wind effect or AWS) (Hounyèmè et al 2023). The negative effects of acidi cation (Bressan et al 2014;Ventura 2018), temperature and salinity on bivalves have also been demonstrated in the literature.…”
Section: Selected Metrics and Coherence Of Metric Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…We can also explain the negative in uence of dredging activities (Observation characteristic of this type of pressure proxy 'Depth') which likely lead to the suspension of sediment in the water column, by its abrasive effects on the eggs, by its reduction of the pumping rate of the bivalves and by their direct mortality (Wilber & Clarke 2001). In the context of Nokoué, resuspension is also driven by waves (wind effect or AWS) (Hounyèmè et al 2023). The negative effects of acidi cation (Bressan et al 2014;Ventura 2018), temperature and salinity on bivalves have also been demonstrated in the literature.…”
Section: Selected Metrics and Coherence Of Metric Responsesmentioning
confidence: 99%
“…This is not very severe compared to the options taken in other studies/areas (Argillier et al (2012b). This may be due to the sampling points not being in a position to re ect the changes in the catchment (Hounyèmè et al 2023). Regarding TKN, the 0.9 mg/L corresponds to the standard lower limit proposed for e uent discharge to surface waters, which is on the order of 100 mg/L (Dash 2013; classes for the quality status obtained in the low salinity areas of the Mira estuary (Portugal) (Medeiros et al 2012).…”
Section: Coherence Of Metrics Reference Values and Thresholdsmentioning
confidence: 99%
See 1 more Smart Citation